Phosphorus accumulates faster than nitrogen globally in freshwater ecosystems under anthropogenic impacts - Yan, Zhengbing; Han, Wenxuan; Peñuelas, Josep; Sardans, Jordi; Elser, James J.; Du, Enzai; Reich, Peter B.; Fang, Jingyun (Ecology letters, 2016)
Combined effects of cumulative nutrient inputs and biogeochemical processes that occur in freshwater under anthropogenic eutrophication could lead to myriad shifts in nitrogen (N):phosphorus (P) stoichiometry in global freshwater ecosystems, but this is not yet well‐assessed. Here we evaluated the characteristics of N and P stoichiometries in bodies of freshwater and their herbaceous macrophytes across human‐impact levels, regions and periods. Freshwater and its macrophytes had higher N and P concentrations and lower N : P ratios in heavily than lightly human‐impacted environments, further evidenced by spatiotemporal comparisons across eutrophication gradients. N and P concentrations in freshwater ecosystems were positively correlated and N : P was negatively correlated with population density in China. These results indicate a faster accumulation of P than N in human‐impacted freshwater ecosystems, which could have large effects on the trophic webs and biogeochemical cycles of estuaries and coastal areas by freshwater loadings, and reinforce the importance of rehabilitating these ecosystems.